DANÇA: linguagem do corpo na educação infantil - Lima, Ruth Regina Melo de (2010)
This production is a reflection about the practices/experiences involving the teaching of the dance developed by the teachers in the Núcleo de Educação Infantil (NEI/UFRN), with the children from 2 to 7 years old, having as objectives: describe and interpret the lived experiences with the dance focusing on the meaning of the dance and organization of the pedagogic job, identify blanks in the pedagogic practices of dance and appoint possible perspectives to the teaching of dance on the infant education. The way from the investigation has begun with the following question: Who do the teachers understand the dance and live it on the Núcleo de Educação Infantil? The research of phenomenological orientation toke as methodological reference the qualitative approach from the placed phenomenon type, this one has as beginning the interest on the phenomenon by the way as it happens on the lived experience from where comes the knowledge with we can present about the world, trying to interpret it, understand it on its essence/existence. The interviews showed that the researched subjects give to the dance different meanings and consequently present variations on the manner to organize the work around this knowledge. The most of the teachers recognizes the dance as a culture expression, being a priority on the school the job with the folkloric dances. They recognize too the dance as knowledge/content coming from the Arts and Physical Education areas and its relation with the knowledge from others areas on the pedagogic action. There were found different process on the way to conduct the job with the dance in relates from experiences done with dance at NEI and, therefore, of teach/learn this knowledge. Its perceptible that exists a systematic work with the objective of develop the dance and its various educative possibilities, starting from the research about its origins, the exploration of the movement, the contextualization until the artistic practice. Those possibilities are reinforced on the school s curricular propose. Some experiences have as a priority the free expression, the dance s vision without context or the reproduction of movements as stand manners of teaching dance, situations like those observed on the investigation as products from the blanks on the academic formation from the teachers with must be fixed. The interpretation of the experiences with dance, described by the teachers from NEI, connected with the theoretical referential from the investigation, allowed to appoint three perspectives to the work with dance in the infant education, having as main interlocutors Merleau-Ponty and Rudolf Laban: the dance as the body s language; the dance and its movement factors; imitate, improvise and play: manners of draw ways to dance. On those process are emphasized the dance on the scholar context, the elements that constitute this language and the forms of appropriate from it supported in a ludicrous, poetic and educative vision, having as focus the children s education on its peculiarities and possibilities